Analysis of Betawi Culture from the Perspective of Professional Ethics in Public Accountants - Muhammad Aras Prabowo; Fauzan Hasim; Habsyah Fitri Aryani (Trescode Green Organization, 2025)
This inquiry points to growing Betawi social values with the code of morals for bookkeepers to extend the polished skill and compliance of bookkeepers with the code of morals. The research method utilized could be a written survey utilizing clear information examination. The writing sources utilized are inquiries about results that are suitable to the inquiry about a point. The comes about gotten within the investigate uncover that there are five Betawi social values that have keenness to strengthen the accountant's code of morals. These values. among others, (1) Legitimate (Betawi workers' ethos is nice and legitimate), (2) Firm (immovable in their position and not effectively affected), (3) Agile (able to work rapidly and productively), (4) Ajer ( slick, careful, grinning), (5) Kitchen insider facts (firm in keeping privileged insights). These five elective values are utilized to reinforce polished skills and uphold the laws and directions of the accountant's code of morals, Particularly with a Betawi social foundation.